Analysis of Legal Protection for Electronic-Based Land Certificate (E-Certificate) Holders in Land Law in Indonesia - Lius, Muhammad Jeppry (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2024)
This research aims to identify, study and analyze legal protection for electronic-based land certificate holders in land law in Indonesia. Apart from that, this research also aims to identify, study and analyze the obstacles faced in efforts to protect the law, as well as finding solutions to deal with these obstacles. The method used is normative juridical legal research. The data used consists of primary data such as the 1945 Constitution, Law Number 5 of 1960 concerning Basic Agrarian Principles Regulations, Law Number 11 of 2008 concerning Information and Electronic Transactions, Government Regulation Number 24 of 1997 concerning Land Registration, Regulations Government Number 71 of 2019 concerning Implementation of Electronic Systems and Transactions, as well as secondary data which includes books and other supporting documents. Data collection was carried out through Document Study and Literature Study. Data analysis was carried out using qualitative descriptive methods. The research results show that legal protection for electronic-based land certificate holders does not cause problems, because the certificate is recognized as valid proof of ownership based on the Electronic Information and Transactions Law (UU ITE), especially regulated in Article 6. Its validity is also strengthened in Article 5 Regulation of the Minister of Agrarian Affairs and Spatial Planning/National Land Agency (ATR/BPN) Number 1 of 2021.